Arts and sciences - Lellouche, Ofer (Frontiers in Human Neuroscience, 2013)
The idea of bringing together these two disciplines is not new. In almost every age, art and science have had a difficult and fragile relationship. Where does this mutual fascination come from? What are the limits of this dialogue? How can we avoid misunderstanding, and manage this encounter in a productive way?